Age-related changes in DNA methylation levels at CpG sites in bull spermatozoa and in vitro fertilization-derived blastocyst-stage embryos revealed by combined bisulfite restriction analysis - KANEDA, Masahiro; ADACHI, Hiromichi; TAKEDA, Kumiko; KOBAYASHI, Eiji; HOSHINO, Yoichiro; IWAO, Ken; AKAGI, Satoshi; NISHINO, Kagetomo; IMAI, Akira; WATANABE, Shinya (Journal of Reproduction and Development, 2019)
Age-associated methylation changes in genomic DNA have been recently reported in spermatozoa, and these changes can contribute to decline in fertility. In a previous study, we analyzed the genome-wide DNA methylation profiles of bull spermatozoa using a human DNA methylation microarray and identified one CpG site (CpG-1) that potentially reflects age-related methylation changes. In the present study, cryopreserved semen samples from a Japanese Black bull were collected at five different ages, which were referred to as JD1-5: 14, 19, 28, 54, and 162 months, respectively, and were used for genome-wide DNA methylation analysis and in vitro fertilization (IVF). Distinct age-related changes in methylation profiles were observed, and 77 CpG sites were found to be differently methylated between young and adult samples (JD1-2 vs. JD4-5). Using combined bisulfite restriction analysis (COBRA), nine CpG sites (including CpG-1) were confirmed to exhibit significant differences in their age-dependent methylation levels. Eight CpG sites showed an age-dependent increase in their methylation levels, whereas only one site showed age-dependent hypomethylation; in particular, these changes in methylation levels occurred rapidly at a young age. COBRA revealed low methylation levels in some CpG regions in the majority of the IVF blastocyst-stage embryos derived from spermatozoa at JD2-5. Interestingly, bulls with different ages did not show differences in their methylation levels. In conclusion, our findings indicated that methylation levels at nine CpG sites in spermatozoa changed with increasing age and that some CpG regions were demethylated after fertilization. Further studies are required to determine whether age-dependent different methylation levels in bull spermatozoa can affect fertility.